The attractiveness of rural tourism as special interest tourism: Case study on natural attractions in Bogor District - Pradana, Triandi; Simamora, Vera; Erwen, Ivana Valencia (Universitas Wiralodra, 2024)
Tourism has become an activity of the needs of society in general, Tourism has become the main necessity of human life so that many tourists want to take a vacation to tourist attractions that they are interested in. There is a gap/problem that can be seen from this phenomenon, namely along with the development of tourism there is a problem called mass-tourism. Mass tourism occurs due to activities focused only on the most popular tourist attractions. This research was conducted to determine the potential for special interest tourism activities in Bogor Regency to minimize potential of mass tourism. The research method used qualitative methods with a case study approach. Data collection carried out is literature review, in-depth interviews, survey, and documentation. The interview data collected was analysed using triangulation techniques. Bogor Regency has a geographical type that falls into the category of rural tourism, which is dominated by highlands and many natural attractions have 20 attractions in the particular interest tourism category. Unique interest tourism attractions such as nature trekking, camping, mountain hiking, forest exploration, tourist / traditional villages, and agro-tourism. Tourists are interested in visiting special interest tourism objects with the highest percentage of 85.7%. The uniqueness and Novelty of this research is done to find out special interest tourism attractions in Bogor regency. The topic of previous research that is used as a reference in this research is tourism potential and tourism development strategies in Bogor regency.